Effect of Job Involvement, Organizational Commitment and Satisfaction on Turnover Intention: A Research in the City of Antalya - AKSU, AKIN; ARSLAN, SELİN; YARDIMCI, EYLEM OLCAY; KAYA, HASAN FAHRETTİN; ERGENÇİÇEĞİ, AYTÜL (Turizam, 2020)
Today like other establishments, touristic establishments are trying to survive under conditions of high-level competition among their rivals. The diversity aspect of jobs in touristic establishments needs analysis to determine operational aspects and outcomes. In this context, to sustain satisfaction and motivation of employees there are critical factors. In this paper, the possible relationships among job involvement, commitment, satisfaction and turnover intention levels of employees were investigated. As a result of the regression analysis, it was concluded that at least one of the independent variables of the model, which were job involvement, organizational commitment, and job satisfaction levels, had an impact on intention to turnover. The findings of the research are important both from theoretical and practical perspectives. From a theoretical perspective, this research shows the possible effect of job involvement, commitment, and satisfaction on turnover intention. From a practical perspective, the results would be of help for tourism sector professionals, researchers and decision makers.
Keywords: Job involvement; commitment; satisfaction; turnover intention; Antalya; Turkey